2020
DOI: 10.18502/ijrm.v13i7.7363
|View full text |Cite|
|
Sign up to set email alerts
|

Does the repeat dose of gonadotropin-releasing hormone agonist trigger in polycystic ovarian syndrome improve in vitro fertilization cycles outcome? A clinical trial study

Abstract: Background: A repeat dose of Gonadotropin-releasing Hormone (GnRH) agonist could provide long duration of luteinizing hormone (LH) surge and amplitude appropriately. Objective: Improvement in oocyte maturity could be obtained by a repeat dose of GnRH agonist. Materials and Methods: In this randomized double-blinded study, 120 women with polycystic ovarian syndrome and serum estradiol level (E2) > 3000 who were candidate for in vitro fertilization with Antagonist protocol were enrolled between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…in women with cervical cancer aged 20-45, and found significant differences in terms of bFSH, bE 2 , AMH and bAFC between the treatment and control groups (31). Further, we found that administering the GNRH-a during chemotherapy provided significant protective effects to the ovary tissue (32).…”
mentioning
confidence: 50%
“…in women with cervical cancer aged 20-45, and found significant differences in terms of bFSH, bE 2 , AMH and bAFC between the treatment and control groups (31). Further, we found that administering the GNRH-a during chemotherapy provided significant protective effects to the ovary tissue (32).…”
mentioning
confidence: 50%